Analisa Rasio Likuiditas Dalam Mengukur Kinerja Keuangan PT. Mustika Ratu, Tbk (Tahun 2010-2016) - Nuriasari, Selvia (Jurnal Riset Bisnis dan Investasi, 2018)
Financial ratio analysis is very important for company, one of which is management that need to analysis of financial performance and the results are used to design business plan, evaluate management and company performance. Liquidity ratio is one of the financial ratios used with the aim of measuring the ability of a company to pay a current liability. and to measure the company's ability to finance the company's operating activities. PT. Mustika Ratu, Tbk is was one of the national companies in the manufacturing sector of herbal medicine, cosmetics and ingredients for beauty care which experienced a decline in sales, which among others was due to the large number of competitors and the entry of products from abroad. A decrease in sales will have an impact on the ability of PT. Mustika Ratu, TBK in fulfilling its liabilites includes current liabilities, especially when it is seen that most of its raw materials are still imported from abroad so there is the possibility of adding "outside funds" to buy these raw materials to meet the needs so that the sales target is achieved. The addition of these obligations, including current liabilities will have an impact on the increase in the burden of PT. Mustika Ratu, TBK in paying current liabilities. So here the researcher is interested in raising the problem, namely seeing the ability of PT. Mustika Ratu, TBK in fulfilling its liabilities in paying current liabilities by using liquidity ratios. The formulas that will be used in analyzing the ability to current liabilities in PT. Mustika Ratu, TBK are current ratio, quick ratio, cash ratio, net working to capital ratio, and inventory to net working capital ratio.